Rational Use of Proton Pump Inhibitors Among the Early Aging Population: Evidence from a Community Health Center in Indonesia - Suryawati, Suryawati; Animalika, Lulu; Narisa, Maghyan; Suardi, Hijra Novia; Aini, Zahratul; Mulia, Vera Dewi; Maghfirah, Desi (Graha Primera Saintifika, 2026)
Proton pump inhibitors (PPIs) are among the most commonly prescribed medications worldwide and are widely used for the management of acid-related disorders, particularly among adults in their early ageing period, where concerns about inappropriate prescribing remain prevalent. This study aimed to evaluate the rational use of PPIs among adults aged ≥46 years at a primary healthcare centre in Banda Aceh, Indonesia. This study focuses on the appropriateness of indications, dosages, and durations, as well as potential drug–drug interactions. Dose appropriateness was assessed using Lexicomp standard adult dosing. Duration and appropriateness of indications were assessed according to the Indonesian Gastroenterology Consensus. A retrospective cross-sectional study was conducted, comprising 1,997 records. A sample of 107 patients who met the predefined inclusion and exclusion criteria was analysed. Most patients were aged 56–65 years and predominantly female, with dyspepsia as the main indication. Omeprazole was prescribed in all cases, commonly at 20 mg twice daily. Nearly half of prescriptions were inappropriate, and appropriate dosing was limited. While treatment duration was generally adequate, some cases were shorter than recommended. Potential drug–drug interactions were identified but were mostly of low clinical significance. Overall, the rational use of PPIs among the patients in this primary healthcare setting remains suboptimal, particularly in terms of indication and dosing. These findings highlight the need to strengthen adherence to clinical guidelines and to implement regular medication reviews to promote safer, more rational PPI use in this population.